Optimization of Bhabinkamtibmas in Preventing Vehicle Theft Crime in Tembalang Police Jurisdiction - Kaisiri, Joris Togap Polaramos (Indonesian Journal of Police Studies, 2024)
The author's final project raises the issue of "How to Optimize Bhabinkamtibmas in the Context of Preventing Theft of Motor Vehicle Theft in the Legal Area of Tembalang Police Station". This Final Project aims to identify the work system of Bhabinkamtibmas and organizational resources of Bhabinkamtibmas Tembalang Police. This research uses a qualitative approach with the type of field research through limited observation, interviews and document studies. The data sources used were also obtained from relevant articles, journal books and online media news. This research uses Management Theory, SWOT Theory and SDO Theory as well as four concepts relevant to the problem, namely the concept of crime prevention, the concept of Bhabinkamtibmas, the concept of community policing and the concept of optimization in accordance with Perkap Number 7 of 2021 concerning Bhabinkamtibmas and Perpol Number 1 of 2021 concerning Community Policing. The results of the study found that the crime of curnmor is the highest crime in the jurisdiction of Tembalang Police. The implementation of Bhabinkamtibmas activities carried out has problems in planning, organizing, implementing and supervising, as well as problems in the human element, budget, infrastructure, and methods. Based on the results of the research, the author suggests that mapping areas of vulnerability, holding cross-functional cooperation, rearranging plans, forming FKPM Kawasan, procuring sarpras and direct supervision by the leadership of the implementation of activities in accordance with Perkap Number 7 of 2021 concerning Bhabinkamtibmas and Perpol Number 1 of 2021 concerning Polmas. To improve human resources, it is necessary to improve the abilities and insights of Bhabinkamtibmas members through discussion forums and training held by the Tembalang Police so that the implementation of activities can be optimized.